LGBTQ+ adolescent and young adult mental and physical wellbeing: examining the effects of non-adapted versus adapted mindfulness-based interventions - Klimo, Kasey D., author; Lucas-Thompson, Rachel, advisor; Shomaker, Lauren, advisor; Brown, Samantha, committee member; Carlson, Laurie, committee member (Colorado State University. Libraries, 2024)
Lesbian, gay, bisexual, transgender, queer and other gender and sexual minority identified (LGBTQ+) adolescents and young adults face mental and physical health disparities compared to their heterosexual and cisgender counterparts. These disparities in health are often due to minority stressors, like experiencing discrimination and oppression. Adolescence and emerging adulthood are vulnerable developmental periods for LGBTQ+ youth and young adults due to the prevalence of minority stressors while also navigating developmental tasks. Mindfulness based interventions (MBI) may be a potential method to intervene upon health disparities in this population, as the mindfulness stress-buffering hypothesis posts MBI may be the most beneficial in populations that experience high levels of stress. Chapter one explores the acceptability, feasibility, and effects of an online MBI, L2B, on sexual minority participants compared to heterosexual participants. Sixty-two college-aged participants completed baseline and post-test questions assessing mental health, mindfulness, self-compassion, emotion regulation, and substance usage (Mage=21.28, SD=4.17, 82.3% Caucasian, 85.5% Non-Hispanic/Latinx, 71% female, 37% LGBQ+). Results from chapter one indicated L2B was acceptable, but feasibility, as indicated by attendance and drop- out rates, could be improved. Furthermore, sexual minority participants saw statistically meaningful improvements in all outcomes except for substance usage and consequences of alcohol use. sexual minority participants may benefit more greatly from MBI related to mental health, internalized shame, consequences of Marjana use, accessing regulation strategies, and with goal-oriented behavior from just as much, or greater than heterosexual participants when related to mental health. However, further research is needed to explore the effects of MBI on substance use among sexual minority participants. Study two explores the initial acceptability and feasibility, along with the effects of an online MBI, L2B-Q, that was adapted specifically to meet the needs of LGBTQ+ adolescents. Twenty adolescents completed baseline and post-test assessments on mental health symptoms, mindfulness, stress-related health behaviors, and identity constructs. Participants also participated in a focus group to provide qualitative feedback on L2B-Q. Results from study two indicate L2B-Q was feasible and accepted, however further adaptations (e.g., changes in timing, and activity modifications) would be beneficial to the program. Furthermore, results indicate than an adapted MBI is highly effective in reducing mental health and stress, while increasing mindfulness and identity related variables. In the final chapter, I compare the effects found in chapter one and chapter two and discuss the ways in which each program differed from one another, and which program may be more effective among LGBTQ+ participants.
Keywords: LGBTQ+ wellbeing; mindfulness-based intervention; health disparities; stress-related health behaviors; mental health